KESANTUNAN BERBAHASA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA 1 TAMPAKSIRING - widiasri, dewaayu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
This research was conducted to illustrate the application of language impressions in Indonesian Learning in SMA 1 Tampaksiring. Data collection methods are nonpartisan observation and an interview method with record techniques. Qualitative methods carry out the use of analysis through practical techniques based on the context of Indonesian Learning. The results showed four principles of language, namely the maxim of wisdom, agreement, praise, and sympathy. This principle of courtesy is used to develop increased effectiveness in learning to create a safe and comfortable classroom atmosphere.